Graphene-Based Nanomaterials: From Production to Integration With Modern Tools in Neuroscience - Kitko, Kristina E.; Zhang, Qi (Frontiers in Systems Neuroscience, 2019)
Graphene, a two-dimensional carbon crystal, has emerged as a promising material for sensing and modulating neuronal activity in vitro and in vivo. In this review, we provide a primer for how manufacturing processes to produce graphene and graphene oxide result in materials properties that may be tailored for a variety of applications. We further discuss how graphene may be composited with other bio-compatible materials of interest to make novel hybrid complexes with desired characteristics for bio-interfacing. We then highlight graphene’s ever-widen utility and unique properties that may in the future be multiplexed for cross-modal modulation or interrogation of neuronal network. As the biological effects of graphene are still an area of active investigation, we discuss recent development, with special focus on how surface coatings and surface properties of graphene are relevant to its biological effects. We discuss studies conducted in both non-murine and murine systems, and emphasize the preclinical aspect of graphene’s potential without undermining its tangible clinical implementation.